Knowledge and understanding of Entrepreneurs’ Tax Filing Service via the TaxRIS System in Xay district Municipality, Oudomxay Province - Phounnaly, phayvanh; XAYYATI , Bouchanh; ANOLAC , Vira (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The purposes of study were: 1) To study the knowledge and understanding of entrepreneurs toward the tax filing service via the TaxRIS system in Xay district Municipality, and 2) to compare of levels of knowledge and understanding on the tax filing service via the TaxRIS system in Xay district Municipality, Oudomxay Province, categorized by personal factors. The research sample was 180 peoples from entrepreneurs in Xay district Municipality, Oudomxay Province by using questionnaires as data collection instrument, and statistics were used to analyze frequency, percentage, mean, standard deviation, t-test and F-test. The research found that: 1) The entrepreneurs in Xay district Municipality demonstrate a moderate understanding of filing tax returns through the TaxRIS system. specifically, regarding the navigation of the official tax declaration website, deadlines for different tax types, and the 500,000 LAK penalty for late submissions. Furthermore, they are informed about the necessary attachments for tax filings, error correction protocols, the 0.1% automatic penalty for late payments, and the official submission channels to government agencies. 2) a comparison of levels of knowledge and understanding on the tax filing service via the TaxRIS system in Xay district Municipality, Oudomxay Province, categorized by personal factors. revealed that: entrepreneurs who differing in business periods held different of knowledge and understanding on the tax filing service via the TaxRIS system. Entrepreneurs differing. Regarding other personal factors, there were no statistically significant differences in the levels of knowledge and understanding of the TaxRIS system at the 0.05 level.